Numerical modelling response of laser welded sandwich panel under three-point bending test - N. K., Romli; M. R. M., Rejab; Xiaoxia, Jiang; Mohamad Nazirul Mubin, Merzuki (IOP Publishing, 2019)
The sandwich structure is known by inner and outer faces which acted compositely with relatively low strength core. Sandwich panel consisted of two thin and stiff skins and separated by a thick and lightweight core. The objective of this study to predict the behaviour of the laser-welded sandwich panel under three-point bending test. Numerical modelling of laser-welded was studied and run under bending loading. The sandwich panels were studied on a different number of the unit cell; 1-core, 2-core and 3-core. The role of a number of web-core to determine overall deformation and local failure response of the sandwich panel was studied. Faceplate and web plate were connected by using diode laser welding. The plates were cut by using sheet metal cutter machine for precise dimension. The sandwich panel modelled by using Abaqus 6.13 version to predict the response of the sandwich panel under bending loading. Cell wall buckling was found as an initial failure in the corrugated core system. The prediction result showed good agreement with experimental measurements.